Evaluasi Penerapan Internal Control dan Pelaksanaan Good Corporate Governance pada PT PLN (Persero) Distribusi Jakarta Raya dan Tangerang - Iswandi Iswandi (Binus Business Review, 2011)
PT. PLN (Persero) Distribusi Jakarta Raya dan Tangerang have implemented Internal Control and Good Corporate Governance. The research would like to evaluate the implementation of Internal Control accordance with COSO’s criteria (Committee of Sponsoring Organizations of the Treadway Commission) and KNKG’s criteria (Komite Nasional Kebijakan Governance). Based on research found that five components of COSO such as control environment, risk assessment, control activities, information and communication, monitoring have been implemented but unfortunately one of the component such as control activities not yet implemented properly accordance with COSO’s criteria. The company also have been imlemented GCG accordance with KNKG’s criteria but still need development through internalization GCG’s spirit among the employees because some employees still have different perception related to GCG. For example from employee stand point there’s no problem receive special gift or receive special payment from customer and have a conflict of interest when deal with public accountant.